TP53 Loss of Heterozygosity Induces De Novo SCLC Formation in EGFR-Mutated Lung Adenocarcinoma: A Case Report - Kei Kunimasa, MD, PhD; Yosuke Hirotsu, PhD; Kenji Amemiya, MSH; Harumi Nakamura, MD, PhD; Kazumi Nishino, MD, PhD; Keiichiro Honma, MD, PhD; Jiro Okami, MD, PhD; Masao Omata, MD, PhD; Toru Kumagai, MD, PhD (JTO Clinical and Research Reports, 2022)
SCLC transformation in EGFR-mutated lung adenocarcinoma is one of the major phenotypic changes that is observed during the resistance to EGFR tyrosine kinase inhibitors. However, the mechanism of this transformation remains unclear. In this study, we found a small de novo SCLC component in surgically resected specimens of EGFR-mutated lung adenocarcinoma before EGFR tyrosine kinase inhibitor treatment. By using laser microdissection and whole-exome sequencing, TP53 loss of heterozygosity was found to be possibly involved in SCLC transformation.